STRATEGI GURU DALAM MENGELOLA KELAS TUNARUNGU DI SLB AYODYA TULADA SURABAYA - Sholehah, Putri Faridatus; Ricca Aulia Rahma; Mafrichatuz Zuhroh; Sayyidati Beta Masbaha Azzahroh; Amalia Nur Vikraini; Nova Estu Harsiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe teachers’ strategies in managing deaf student classrooms at SLB Ayodya Tuladha Surabaya and the adaptation process of strategies applied during learning activities. This research employed a descriptive qualitative approach involving deaf classroom teachers and the principal as research subjects. Data were collected through non-participant observation, semi-structured interviews, and documentation. The results showed that classroom management for deaf students was conducted adaptively and dynamically through the use of sign language, visual media, material repetition, individual approaches, and seating arrangements. Teachers continuously adjusted learning strategies based on students’ nonverbal responses, level of understanding, and participation during the learning process. The main obstacles found were differences in communication abilities and students’ comprehension levels within one classroom, as well as limited learning time. However, these challenges could be addressed through teachers’ flexibility in adjusting learning pace, media, and communication techniques. This study confirms that the effectiveness of learning for deaf students is strongly influenced by teachers’ ability to adapt strategies in real-time and contextually during classroom instruction.